Effect of past century mining activities on sediment properties and toxicity to freshwater organisms in northern Sweden - Lidman, Johan; Olid, Carolina; Bigler, Christian; Berglund, Asa M. M. (2023)
The release of toxic metals from local mining activities often represents a severe environmental hazard for nearby lake ecosystems. Previous studies on the impact of mining have primarily focused on single lakes, with less emphasis on spatial and temporal recovery patterns of multiple lakes within the same catchment, but with different hydrological connection and distance to the pollutant source. This knowledge gap prevents us from assessing the real environmental risk of abandoned mines and understanding ecosystem recovery. This study explores the intensity and spatial patterns of sediment contamination and the potential for ecosystem recovery in three lakes in close vicinity of a lead (Pb) and zinc (Zn) mine in Sweden that has been inoperative for >20 years. Dated (210Pb and 137Cs) sediment cores from each lake were used to reconstruct temporal patterns in trace element deposition and relate those with past mining activities. Results show that all lakes were affected by mining, indicated by increasing Pb and Zn concentrations and decreasing organic matter content, at the onset of mining. However, the extent and timing of mining impact differed between lakes, which was partly ascribed to differences in the historical use of tailings and settling ponds. Assessment of toxicity levels in sediments, based on normalized Probable Effect Concentration Quotient (PEC-Q) to organic matter content, provided more consistent results with the historical mining than conventional methods, showing a decreasing impact in lakes once the operations ceased. Still, sediment Pb concentrations were > 10 times higher than pre-mining values, evidencing the urgent need for remediation actions in the study lakes. This study highlights the importance of considering spatial heterogeneity in metal deposition, sediment organic matter content, and hydrological connectivity with tailings when risk assessments are performed in mining-impacted lakes. The use of normalized PEC-Q in toxic assessments is also recommended.